Ocimum basilicum Essential Oil Modulates Hematotoxicity, Oxidative Stress, DNA Damage, and Cell Cycle Arrest Induced by β-cyfluthrin in Rat Liver - Ali B. Jebur; Raghda A. El-Sayed; Fatma M. El-Demerdash (Frontiers Media S.A., 2022)
Pesticides are used in large quantities infrequently, resulting in environmental damage and health issues. The goal of the current study was to explore the ameliorating effect of Ocimum basilicum (Basil) leaves essential oil versus the harmful effects of β-cyfluthrin in rat liver. Male Wistar rats were classified at random into four groups; negative control (corn oil), basil leaves essential oil (BEO, 3 ml/kg), β-cyfluthrin (positive control) (β-Cyf; 15 mg/kg BW, 1/25 LD50), and BEO plus β-Cyf, respectively. The rats were given their doses orally every day for a month. Results revealed that BEO yielded 6.32 mg/g with 33 identified components, representing 97% of the total oil. BEO implicated a considerable level of total phenolic contents, DPPH radical scavenging capacity, ABTS activity, and FRAP. The treatment of β-Cyf dramatically elevated lipid peroxidation (TBARS and H2O2) (LPO), protein oxidation (PC, AOPP, and HYP), and considerably reduced enzymatic (SOD, CAT, GPx, GR, and GST) and non-enzymatic (GSH) antioxidants. After β-Cyf treatment, hematological parameters, body and liver weights, enzyme activity (AST, ALT, ALP, and LDH), as well as protein, albumin, globulin, and total bilirubin levels were all considerably affected. Furthermore, β-Cyf increased the expression of pro-inflammatory genes (TNF-α, IL-6) as well as DNA damage and cell cycle arrest in the G0/G1 phase and decreased the number of cells in S and G2/M phase of liver cells. Moreover, rats given BEO then intoxicated with β-Cyf showed substantial changes in the majority of the parameters tested. Finally, BEO was shown to have high antioxidant efficacy in combating β-Cyf toxicity because of its high phenolic content.